Study protocol of a randomized controlled trial on two new dissemination strategies for a brief, shared-decision-making (SDM) training for oncologists: web-based interactive SDM online-training versus individualized context-based SDM face-to-face training - Müller, Nicole; Gschwendtner, Kathrin M.; Eich, Wolfgang; Bieber, Christiane (Trials, 2019)
Oncological patients often feel left out of important treatment decisions. However, when physicians engage them in shared decision-making (SDM), patients benefit in many ways and the situation is improved. SDM can effectively be taught to physicians, but participation barriers for SDM physician group trainings are high, making it hard to convince physicians to participate.